2014
DOI: 10.1596/978-1-4648-0280-5
|View full text |Cite
|
Sign up to set email alerts
|

Demand and Supply of Skills in Ghana: How Can Training Programs Improve Employment and Productivity?

Abstract: Some rights reserved 1 2 3 4 17 16 15 14 World Bank Studies are published to communicate the results of the Bank's work to the development community with the least possible delay. The manuscript of this paper therefore has not been prepared in accordance with the procedures appropriate to formally edited texts. This work is a product of the staff of The World Bank with external contributions. The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of The World… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 7 publications
2
46
0
Order By: Relevance
“…A key participant said:
“During my time at my previous organisation, one of the comment I use to hear is that oh…………..the Ghanaian [worker] is an expert at passing examinations. That was some of the comments the Expats [Expatriates] use to say and they think, oh they have just passed their exams but they're not solid [they don't imbed the practical skills and knowledge] that kind of thing” [SK4, IN3].
Other challenges with the educational system that were identified included low‐quality teaching and learning, poor quality of technical and science education, poor infrastructure and poor management, and the lack of supervision among others (Bawakyillenuo, Akoto, Ahiadeke, Aryeetey, & Agbe, ; Darvas & Palmer, ; National education sector performance report, ).…”
Section: Dimension: Education and Training Arrangementssupporting
confidence: 87%
See 2 more Smart Citations
“…A key participant said:
“During my time at my previous organisation, one of the comment I use to hear is that oh…………..the Ghanaian [worker] is an expert at passing examinations. That was some of the comments the Expats [Expatriates] use to say and they think, oh they have just passed their exams but they're not solid [they don't imbed the practical skills and knowledge] that kind of thing” [SK4, IN3].
Other challenges with the educational system that were identified included low‐quality teaching and learning, poor quality of technical and science education, poor infrastructure and poor management, and the lack of supervision among others (Bawakyillenuo, Akoto, Ahiadeke, Aryeetey, & Agbe, ; Darvas & Palmer, ; National education sector performance report, ).…”
Section: Dimension: Education and Training Arrangementssupporting
confidence: 87%
“…The study found that the host country's educational and training arrangements placed strong emphasis on academic qualifications with little recognition of practical skills, especially vocational and technical skills training (Darvas & Palmer, ). One major issue identified by participants was the way the country and some organizations have, over the years, placed too much emphasis on employee qualification and less significance on employee competence and performance.…”
Section: Dimension: Labor Market Conditionssupporting
confidence: 87%
See 1 more Smart Citation
“…Funding and equipping TVET institutions is a vital policy and strategy to draw the map for policymakers to be taken into account (AU, 2007). Furthermore, TVET institutions are more expensive in comparison to other institutions that offer other kinds of education (Darvas & Palmer, 2014). Studies revealed that poor facilities, inappropriate equipment and under-funding were the common criticisms from TVET in developing countries which impacted on institutions to purchase the significant tools so as to improve the quality of TVET (RMoE, n.d.).…”
Section: Financial Supportmentioning
confidence: 99%
“…Despite existing attempts at skills training, the skills gap remains relatively large, as has been noted by a number of researchers. Darvas and Palmer (2014), for example, found a shortfall of 60,000 skilled artisans in the construction sector, with the dearth projected to increase to as many as 250,000 by 2020. A large proportion of the Ghanaian construction industry's growth originates from its residential market, followed by commercial and retail shopping, heavy engineering (especially road works), and multi-storey and high-rise buildings.…”
Section: Skilled Labourmentioning
confidence: 99%